2010
DOI: 10.1111/igc.0b013e3181d224c8
|View full text |Cite
|
Sign up to set email alerts
|

Can We Predict Vesicovaginal or Rectovaginal Fistula Formation in Patients With Stage IVA Cervical Cancer?

Abstract: The risk to develop vesicovaginal and/or rectovaginal fistulae is high after curative radiotherapy with or without chemotherapy and/or hyperthermia in patients with stage IVA cervical cancer. We could not identify further pretreatment factors that might have predicted fistula formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 19 publications
7
20
0
5
Order By: Relevance
“…Several researchers reported the outcome for Stage IVA patients treated with RT alone or CCRT. Those reports showed that survival rates for Stage IVA disease were between 10% and 42%, and LC rates were between 18% and 61% [3, 2326]. In the present study of C-ion RT, 3yOS and 3yLC for Stage IVA patients were 47% and 66%, respectively.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Several researchers reported the outcome for Stage IVA patients treated with RT alone or CCRT. Those reports showed that survival rates for Stage IVA disease were between 10% and 42%, and LC rates were between 18% and 61% [3, 2326]. In the present study of C-ion RT, 3yOS and 3yLC for Stage IVA patients were 47% and 66%, respectively.…”
Section: Discussionsupporting
confidence: 42%
“…Biewenga et al . reported that 22% of treated patients developed vesicovaginal fistula at a median time of 9 months [23], and Moore et al . reported that 48% developed vesicovaginal fistula at a median time of 2.9 months [25].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of symptoms including leaking urine or stools, persistent bleeding, vulnerability to infection and unbearable pain, patients may suffer significant physical, social and psychological distress which negatively impacts on their quality of life [ 24 , 25 ]. The incidence of radiation-induced fistulas was estimated as between 1 % and 4 % for all-comers, while this number can be as high as 22–48 % for more advanced stages, which is similar to our findings [ 24 , 26 ]. In the current series, the incidence of fistula and SCRP (as the main symptoms of patients who underwent surgery) in the RRT group was significantly higher than that in the RS + RT group (17.4 % vs 5.8 % [ p = 0.020] and 10.9 % vs 1.7 % [ p = 0.027], respectively).…”
Section: Discussionsupporting
confidence: 92%
“…They observed an incidence of recto-sigmoid morbidity of < 4 % with doses below 75 Gy and 9 % with higher doses; for the small intestine the incidence of morbidity was < 1 % after a total dose of ≤50 Gy, 2 % after 50–60 Gy and 5 % after higher doses. Previous series have noted a variety of risk factors for severe late toxicities, but common predictors tend to include advancing tumour stage, previous pelvic radiotherapy, the use of RS, an active smoking habit and elevated RT doses [ 29 , 11 , 26 ]. The poor wound-healing characteristics that increase susceptibility to fistula development can largely be attributed to sclerosis in small and medium sized blood vessels, relative tissue hypoxia and soft tissue fibrosis that occurs following RT [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elles concernent environ 10 % des patients. Les fistules vésico-vaginales sont rares et le risque est d'autant plus important que la tumeur initiale envahissait la vessie et/ou le rectum (stade FIGO IVA) [49]. Exceptionnelles, les sténoses urétérales peuvent se manifester par une douleur lombaire liée à l'hydronéphrose en amont.…”
Section: Toxicité Urinaireunclassified